Formation of competence in the field of intellectual property rights protection for employees of institutions of general secondary education within the framework of advanced training - Luniachek, V.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2019)
Тhe paper analyzes scientific sources concerning the protection of intellectual property rights of the pedagogical staff, namely, studies conducted by employees of specialized departments of higher education institutions of Ukraine, domestic scholarly research works, monographic works, academic research works dealing with the issue of advanced training in this sphere, and foreign sources. Furthermore, the article presents the analysis of curricula at Bachelor's and Master's levels regarding the formation of competences of future teachers in the field of intellectual property protection. The results of the analysis prove that there is now an urgent need for advanced training of the general secondary education teaching staff in relation to their awareness of intellectual property protection. The conceptual model of advanced training of general secondary education teaching professionals in the field of intellectual property protection is developed, which offers three options for improving qualifications of the teaching staff of general secondary education institutions in the field of intellectual property protection through the module "Academic Integrity" within the framework of the standard qualification program, through a special course on "Methodology of managing objects of intellectual property" as a separate training unit on a cumulative basis, or through a complete course of advanced training, which comprises full-time and distance learning, in the field of intellectual property protection in the system of general secondary education. Each version is described in detail and presented in the form of educational programs. Furthermore, the article offers models for the advanced training of general secondary education teachers in the field of intellectual property protection at the district level and on the basis of the institution of general secondary education. It has been determined that curricula of higher education institutions, which prepare future teachers and education managers, need to be corrected. The article also emphasizes the need to address the issue of personnel provision for the process of advanced training of the pedagogical staff in the field of intellectual property protection. Due to the fact that professional competence in this sphere is rather specific and integrates knowledge on economic, legal, technical, humanitarian sciences, information technology, etc., the paper suggests that only higher education institutions which have specialized departments provide such services.